The high-energy tail of energetic electron precipitation: solar wind drivers and geomagnetic responses - Salice, Josephine; Nesse, Hilde; Partamies, Noora; Kilpua, Emilia; Kavanagh, Andrew; Decotte, Margot; Babu, Eldho; Smith-Johnsen, Christine (Frontiers in Astronomy and Space Sciences, 2024)
Compositional NOx changes caused by energetic electron precipitation (EEP) at a specific altitude and those codependent on vertical transport are referred to as the EEP direct and indirect effect, respectively. The direct effect of EEP at lower mesospheric and upper stratospheric altitudes is linked to the high-energy tail of EEP (≳ 300 keV). The relative importance of this direct effect on NOx, ozone, and atmospheric dynamics remains unresolved due to inadequate particle measurements and scarcity of polar mesospheric NOx observations. An accurate parameterization of the high-energy tail of EEP is, therefore, crucial. This study utilizes EEP flux data from MEPED aboard the POES/Metop satellites from 2004 -2014.Data from both hemispheres (55-70 • N/S) are combined in daily flux estimates. 164 peaks above the 90th percentile of the ≳ 30 kev flux are identified. These peaks are categorized into absolute E1 and E3 events representing weak and strong ≳ 300 keV responses, respectively. A subset of absolute E1 and E3 events with similar ≳ 30 keV responses is termed overlapping events. Additionally, relative E1 and E3 events are determined by the relative strength of the ≳ 300 keV response, scaled by the initial ≳ 30 keV flux. A comparison between E1 and E3 events aims to identify solar wind and geomagnetic conditions leading to high-energy EEP responses and to gain insight into the conditions that generate a high-energy tail, independent of the initial ≳ 30 keV flux level. Superposed epoch analysis of mesospheric NO density from SOFIE confirms an observable direct impact on lower mesospheric chemistry associated with the absolute E3 events. A probability assessment based on absolute events identifies specific thresholds in the solar wind-magnetosphere coupling function (epsilon) and the geomagnetic indices Kp*10 and Dst, capable of determining the occurrence or exclusion of absolute E1 and E3 events. Elevated solar wind speeds persisting in the recovery phase of a deep Dst trough appear characteristic of overlapping and relative E3 events. This study provides insight into which parameters are important for accurately modeling the high-energy tail of EEP.